(untitled) (Research, Society and Development, 2024)
Mental health is a pillar for the athlete’s performance as a whole, so awareness that mental and physical health must be balanced is the key to a healthy life. As this is a topic little explored in the sporting field, the present study aims to analyze the impact caused by restricted diets on the mental health of athletes, as well as understanding the complications caused by specific dietary restrictions, caused by individuals involved in sports. The basic idea was to verify which disorder is most present and which external factors influence the development of such conditions. The work covers recent research mainly in the area of sports nutrition, with a literature review focused on the psychological bias of mental health. This work contributes to understanding the relationship between restrictive diets and mental health, providing support for the promotion of healthy eating practices. Different types of diets were analyzed, mainly calorie restriction and specific dietary patterns commonly observed in sports. The analysis led to possible effects observed in these practices, exploring disorders such as anxiety, depression, self-esteem and body image. Articles were analyzed in the SCIELO databases, CAPES journal portal, PubMed and Google Scholar.